The Influence of Value Creation and Image on the Performance of the Museum of the Struggle for Independence History of the Republic of Indonesia - Rizkie Widokarti, Joko; Kartini, Dwi; Marty Oesman, Yevis; Sari, Diana (Opción, 2019)
The performance of historical-based tourism in Indonesia is still relatively low. One of the tourism destinations is the history museum. This condition is allegedly caused by the problem of low image of Museum tourist destination when com- pared with other destinations, as well as problems in the aspects of value creation. So based on the background, this study aims to examine the influence of value creation and image in influencing the performance of museum of the struggle for independence history of the Republic of Indonesia. This research uses applied re- search method based on quantitative data type. The time horizon is cross sectional, because this research is done at a certain time. The unit of analysis is the museum of the struggle for independence history of the Republic of Indonesia with the observation unit is the management of the Museum throughout Indonesia with a sample of 30. The design of the analysis used to test the hypothesis and to know the relationship between research variables is Partial Least Square (PLS). The re- sults show that value creation and image affect the performance of the museum both simultaneously and partially, which is the image has a greater influence than value creation. So hopefully the results of this study can be applied by the museum managements to improve their performance through the development of a museum image that is supported by the development of value creations.